Analisis kegagalan dan evaluasi sisa umur duplex filter tank akibat corrosion under insulation pada sistem heat recovery steam generator kapasitas 300.000 BCWEPD - Aidil Dwi Anugerah; Priyo Tri Iswanto; Viktor Malau (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
A duplex filter tank in a heat recovery steam generator (HRSG) system which has been operating for 18 years experienced an unplanned shutdown due to leakage. Duplex filter tank consists of two tanks which are covered by an insulation to maintain the temperature of the feedwater as the main source of steam production in HRSG. However, along with continuous operation as well as tanks located in a humidity environment, this will affect the degradation of tank thickness due to corrosion under insulation (CUI). Then, it will lead to leaks resulting in unplanned shutdown and loss steam production opportunity (LPO). This study aims to examine the failure model and the root causes of failure in order to increase the reliability of the unit as well as the appropriate recommendations for preventing CUI in tank and piping systems. The object of this research is the existing duplex filter tank sample and the new duplex filter tank sample. The research method used to determine the condition of the two samples was visual observation, microstructure observation, chemical composition test, tensile test, hardness test, and corrosion rate test. The results showed that the corrosion under insulation (CUI) at the bottom of the duplex filter tank was evenly distributed and at one point occurred due to the thickness of the tank that had exceeded the permissible limit. The root cause of the failure is due to a gap between the insulation and the tank which allow the environment and rainwater to enter and be trapped under the insulation.